Kinesitherapy in amyotrophic lateral sclerosis - Iłżecka, Joanna (Journal of Education, Health and Sport, 2017)
Introduction and purpose of work. Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease of unknown etiology. As a result, damage to motor neurons in patients with clinical symptoms such as weakness and atrophy of muscles, spasticity, paresis, disorders of speech and swallowing difficulties. In view of the lack of effective treatment, it is important causal symptomatic treatment and rehabilitation, including kinesitherapy. The aim of this study was to review the literature concerning the use of kinesitherapy in the ALS. Brief description of the state of knowledge. The evidence regarding the benefits of kinesitherapy in the ALS is limited to a few experimental studies and clinical trials. Experimental studies confirm the beneficial neuroprotective effect of kinesitherapy on motoneurons. Clinical trials have shown the beneficial effect of moderate exercise on the state of ALS patients. It is recommended to exercise: stretching, aerobic, resistance, strengthening and balance, as well as special methods such as the method Vojta and PNF. Literature data show that exercise influence on the activity of motoneurons which are more resistant to apoptosis selectively. Summary. Kinesitherapy is recommended for patients already in the early stages of ALS. However, despite the presented advantages of this method are the need for a more randomized trials on a larger group of patients.